Determination of just-suspension speed for Rushton Turbine using tank bottom pressure measurements - Abdul Raman, Abdul Aziz; Ibrahim, Shaliza; Parthasarathy, R. (1999)
Tank bottom pressure was measured with manometers at five specific locations for a 0.2 m diameter standard cylindrical vessel stirred with Rushton Turbine (6DT). Glass Ballotini bits at 10, 20, 30, 40, 50 and 60 wt/wt were be suspended in water and compressed air at 1, 3 and 5 mm/s superficial gas velocities were used. Plots of pressure versus impeller speed indicates that near the just-suspension speed, the base pressure values show a tendency to either decrease or remain constant after increasing with speed at lower impeller speeds. It was also observed that at the last point of suspension, i.e. at the center of the tank for 6DT, a marked reduction in pressure values occurs after the particles were all suspended, indicating that the tank bottom pressure could be used as an objective means of determining the just-suspension speed.